DI BALIK ANGKA: MENGGALI KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL HOTS - Jahring Jahring; Wilda Purnamasari; Nasruddin Nasruddin (Universitas Muhammadiyah Semarang, 2025)
This study aims to describe the creative thinking abilities of high school students, both overall and based on indicators of creative thinking abilities. The research subjects were 25 students from class XI at SMA Negeri 1 Wundulako, Kolaka, Southeast Sulawesi, Indonesia. This study is a descriptive study using totally sampling technique. The research instrument used a creative thinking ability test. The indicators of creative thinking ability measured included fluency, flexibility, originality, and elaboration. The results showed that: (1) overall, the creative thinking ability of students, with a percentage score of 65.63%, was in the good category; and (2) creative thinking ability based on indicators, namely student fluency was 58.67% (sufficient), student flexibility was 79.33% (good), student originality was 82% (very good), and student elaboration was 42.5% (sufficient). This indicates that students' creative thinking skills are quite optimal because they have successfully applied student-centered learning and are accustomed to working on open-ended and non-routine problems that are complex in nature.